KEY DRIVERS OF FIRM VALUE IN INDONESIA’S PROPERTY AND REAL ESTATE SECTOR - Hartono, Gabriella Charissa; Yanti, Yanti (International Journal of Application on Economics and Business, 2025)
Maximizing firm values, as shown in the company’s stock prices, represents a long-term goal for companies. The firm value is impacted by various factors such as financial performance, tax avoidance, investment decisions, and funding decisions. The study explores the connection between financial performance, tax avoidance, investment decisions, and funding decisions on firm value in property and real estate companies listed on the IDX from 2019 to 2023. Financial performance is assessed using Return on Assets (ROA), tax avoidance by Cash Effective Tax Ratio (CETR), investment decisions through the Price-to-Earnings Ratio (PER), and funding decisions through the Debt-to-Equity Ratio (DER). The study analyzed 50 data from 13 companies using a purposive sampling technique. The research utilized secondary data from financial statements and annual reports published on the IDX, analyzed through multiple linear regression. The findings show that financial performance has a positive and significant impact on firm value. Investment decisions also have a positive and significant impact on firm value. However, tax avoidance does not have a significant impact on firm value, and funding decisions likewise do not have a significant impact. The results suggest that in order to increase firm value, property and real estate firms should focus on improving their financial performance and making optimal investment decisions.